Synthesis of a new glyoxime derivative, characterization and investigation of its complexes with Ni(II), Co(II), Cu(II) and UO2(VI) metals - Tas, E; Cukurovali, A; Kaya, M (Taylor & Francis Ltd, 1998)
In this study, a novel dioxime having the 1,3-oxolane group, 1,2-dihydroxyimino-3,7-diaza-9,10-O-cyclohexylidene decane (H2L), has been synthesized from the reaction of 1,2-O-cyclohexylidene-4-aza-7-amino heptane and anti-chloroglyoxime. Complexes of this ligand with Ni(II), Co(II), Cu(IL) and UO2(VI) salts were prepared. The structure of the ligand and its complexes is proposed from the H-1 and C-13-NMR, IR, mass spectral data, elemental analysis and magnetic susceptibility measurements. In addition, thermal properties of H2L and its complexes were also investigated by thermogravimetric analyses (TGA) and differential thermal analyses (DTA).
Keywords: dioxime; glyoxime; nickel(II); cobalt(II); copper(II)